Evaluation of pancreatin stability through enzyme activity determination - Terra Gleysson De Paula; Vinícius De Farias Marcus; Trevisan Marcello Garcia; Garcia Jerusa Simone (Acta Pharmaceutica)
Pancreatin is a biotechnological product containing an enzyme complex, obtained from porcine pancreas, that is employed in treating pancreatic diseases. Experiments regarding the stability of the pharmaceutical formulation containing pancreatin were performed using standard binary mixtures with 6 excipients in a 1:1 ratio (m/m) and a commercial formulation. To accomplish these goals, samples were stored for 1, 3 and 6 months at 40 ± 1 °C and 75 ± 5 % relative humidity (RH) and 40 ± 1 °C and 0 % RH. Stress testing was also performed. All samples were analyzed to evaluate the α-amylase, lipase and protease activities through UV/Vis spectrophotometry. The results revealed that the excipient proprieties and the storage conditions affected enzyme stability. Humidity was a strong influencing factor in the reduction of α-amylase and protease activities. Stress testing indicated that pH 9.0 and UV light did not induce substantial alterations in enzyme activity.